Does mobility of educated workers undermine decentralized education policies? - Christiane Schuppert (Universität Dortmund, Wirtschafts- und Sozialwissenschaftliche Fakultät, 2007)
The present paper studies a multi-jurisdictional framework, in which, from a federal perspective, educational subsidies turn out to be efficiency enhancing. However, in the presence of mobile high-skilled labor, local jurisdictions might try to free-ride on other regions' education policies and abstain from subsidizing education. Social mobility is introduced as an additional dimension of labor mobility. Using this framework, it is shown that local governments abide by the optimal decision rule for subsidizing human capital investments. Hence, decentralized education policies remain to be efficient, although high-skilled workers are perfectly mobile. Only if one allows for high- and low-skilled mobility, local incentives to promote education vanish.
Keywords: H77; F22; H21; 330; fiscal federalism; migration; optimal taxation; Bildungspolitik; Bildungsinvestition; Subvention; Finanzföderalismus; Arbeitsmobilität; Optimale Besteuerung; Theorie